2014
DOI: 10.1094/phyto-06-13-0148-r
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pathogenicity, Biocontrol Efficacy, and Multilocus Sequence Typing of Verticillium nonalfalfae from the Invasive Ailanthus altissima and Other Hosts

Abstract: Verticillium wilt, caused by Verticillium nonalfalfae, is currently killing tens of thousands of highly invasive Ailanthus altissima trees within the forests in Pennsylvania, Ohio, and Virginia and is being considered as a biological control agent of Ailanthus. However, little is known about the pathogenicity and virulence of V. nonalfalfae isolates from other hosts on Ailanthus, or the genetic diversity among V. nonalfalfae from confirmed Ailanthus wilt epicenters and from locations and hosts not associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
43
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 34 publications
3
43
0
1
Order By: Relevance
“…E. validus is a temperate species with broad tree host range (Rabaglia et al, 2006); a population increase has been documented on the invasive Asian tree of heaven (Ailanthus altissima (Mill.) Swingle) symptomatic for Verticillium wilt in eastern North America (Kasson et al, 2014). E. interjectus is a subtropical species spreading throughout the Southeastern US (Atkinson, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…E. validus is a temperate species with broad tree host range (Rabaglia et al, 2006); a population increase has been documented on the invasive Asian tree of heaven (Ailanthus altissima (Mill.) Swingle) symptomatic for Verticillium wilt in eastern North America (Kasson et al, 2014). E. interjectus is a subtropical species spreading throughout the Southeastern US (Atkinson, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This soilborne fungus was discovered in 2002-2003 naturally killing thousands of Ailanthus trees within a large Ailanthus stand in the forests of south-central Pennsylvania (Schall & Davis, 2009a, 2009b. To date, this potential mycoherbicide has been isolated from infected Ailanthus in Pennsylvania, Virginia and Ohio and may be native to eastern forests (Kasson, Short, et al, 2014;Rebbeck et al, 2013;Schall & Davis, 2009a;Snyder et al, 2013). Aetiology and efficacy studies, using V. nonalfalfae isolate VnAa140 (previously PSU 140), have shown that V. nonalfalfae is extremely virulent on Ailanthus (Kasson, Short, et al, 2014) and rapidly transmitted from diseased to healthy Ailanthus trees by intraspecific root grafts .…”
Section: Introductionmentioning
confidence: 99%
“…To date, this potential mycoherbicide has been isolated from infected Ailanthus in Pennsylvania, Virginia and Ohio and may be native to eastern forests (Kasson, Short, et al, 2014;Rebbeck et al, 2013;Schall & Davis, 2009a;Snyder et al, 2013). Aetiology and efficacy studies, using V. nonalfalfae isolate VnAa140 (previously PSU 140), have shown that V. nonalfalfae is extremely virulent on Ailanthus (Kasson, Short, et al, 2014) and rapidly transmitted from diseased to healthy Ailanthus trees by intraspecific root grafts . Not only does V. nonalfalfae effectively kill the above-ground stem, it also kills the roots and subsequent root suckers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…& Arn. and Acer pensylvanicum L. caused by V. nonalfalfae (Hibben 1959;Harrington and Cobb 1984;Kasson et al 2014), and wilt of Liriodendron tulipifera L. caused by both V. dahliae and V. albo-atrum (Donohue and Morehart 1978), all reports of Verticillium wilt in trees are related to V. dahliae. Although no exact statistics exist on the number of species that are susceptible to Verticillium dahliae, it is estimated that at least 300 (Berlanger and Powelson 2005) to 400 (Klosterman et al 2009) plant species, ranging from herbaceous annuals to woody perennials, are affected.…”
Section: Introductionmentioning
confidence: 99%